Pelayanan Publik Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu di Kabupaten Bulukumba - Subarling Subarling; Andi Rasyid Pananrangi; Syamsul Bahri (Publik : (Jurnal Ilmu Administrasi), 2020)
This article discuss about the level of effectiveness of public services One Stop Investment Service and Integrated Services regarding the management and issuance of Building Permit at Bulukumba Regency. The Office of Investment and Integrated Services (DPMPTSP) with the service unit for the management and issuance of the Buidling Permit is in the category of the most visited by the people in Bulukumba Regency. This condition has an impact on the high frequency of public services that occur in these service units, so it is necessary to know the level of service effectiveness. This study used a survey approach to employees of the Building Permit Service Unit and the community who use the Building Permit service. The data collection technique used a questionnaire. The data analysis technique used frequency tabulation and a Likert scale as the rating scale. Overall, the results of this study indicate that the level of effectiveness of public services at the Investment and Integrated Services Office is in the 'Good' category or the 'Effective' category. The conclusion of this study is that basically public services at the Investment and Integrated Services Office have been going well and have received a good response from the community who use Building Permit services even though this still requires maximum efforts from the local government of Bulukumba Regency to improve these services.Artikel ini membahas tentang tingkat keefektifan pelayanan publik pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Bulukumba terkait pengurusan dan penerbitan IMB. Dinas Penanaman Modal dan Pelayanan Terpadu (DPMPTSP) dengan unit layanan pengurusan dan penerbitan IMB terkategori paling ramai dikunjungi masyarakat. Kondisi tersebut berdampak pada tingginya frekuensi layanan publik pada unit layanan tersebut sehingga perlu diketahui tingkat efektifitas pelayanannya. Penelitian ini menggunakan pendekatan survei terhadap pegawai pada Unit Layanan IMB dan masyarakat pengguna layanan IMB tersebut. Teknik pengumpulan data menggunakan angket. Teknik analisis data menggunakan tabulasi frekuensi dan Skala Likert sebagai skala penilaian. Secara keseluruhan, hasil penelitian menunjukkan bahwa tingkat efektifitas pelayanan publik pada Dinas Penanaman Modal dan Pelayanan Terpadu terkategori ‘Baik’ atau terkategori ‘Efektif’. Kesimpulan penelitian ini adalah pada dasarnya pelayanan publik pada Dinas Penanaman Modal dan Pelayanan Terpadu telah berlangsung baik dan mendapat respon yang baik dari masyarakat pengguna jasa pelayanan IMB meskipun hal tersebut masih memerlukan upaya maksimal dari pemda Kabupaten Bulukumba untuk meningkatkan pelayanan tersebut.